The The role of the press in the history of poetry from Rio Grande do Sul: reflections based on the works of Donaldo Schüler and Luís Augusto Fischer (Ágora Journal, 2023)
This article proposes to reflect on the role of the press in the history of Rio Grande do Sul poetry from the works A poesia no Rio Grande do Sul, by Donaldo Schüler, and Um passado pela frente: poesia gaúcha ontem e hoje, by Luís Augusto Fischer. For this, we resort to the contributions of the history of literature and its articulation with the history of the press. In order to carry out the proposal, methodologically, a bibliographic research was applied, with the intention of understanding the role of the press (and journalism) in literary history. For the analysis technique, the content analysis was listed, which makes it possible to trace the traces about the press and the gaúcha poetry in the two works. Finally, it was identified that the press is present in several decisive and rupture moments in the history of Rio Grande do Sul poetry.
Keywords: press; history of literature; gaúcho poetry; Rio Grande do Sul